Judicial Approaches to Damages in Breach of Contract Cases in Nepal - Rawal, Khagendra (NPRC Journal of Multidisciplinary Research, 2025)
Breach of contract is the condition in which at least one party do not fulfill their respective obligation even after entering into the contract. The aggrieved party can claim the lawful remedies to address the injury suffered. Damage is one of the remedies and can be defined as monetary compensation paid to the innocent party for the breach of contract. This article focuses on investigating the legal and judicial responses to damages in breach of contract cases in Nepal. This doctrinal study has adopted exploratory descriptive and analytical method. This study has used primary data obtained from diverse sources like statutory laws, legal documents, academic journals, reports and precedents established by the Supreme Court of Nepal. The National Civil Code, 2074 had adopted the internationally accepted principle and provisions of damage in Nepal. This paper aims to investigate the principle of specific damage of contract and to discuss the judicial responses to the doctrine of damage of contract in Nepal.